2016
DOI: 10.1039/c6ra22163g
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic and chemogenic synthesis of TiO2NPs via hydrothermal route and their antibacterial activities

Abstract: Novel biogenic and chemogenic sources were used for the synthesis of TiO2NPs with size of NPs for biogenic smaller than chemogenic. From Agar well diffusion method the biogenic synthesized TiO2NPs show more effective antibacterial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The bands at 2923 and 1534 cm À1 attributed to O-H stretching of carboxylic acid and N À H bending of amide, respectively. The bands at 1221 and 1072 cm À1 corresponded to C À N and N-H stretching, respectively [18,19]. These results revealed that presented bacterial biomolecules in the CLS played an important role in the bioreduction of FTN.…”
Section: Characterizationmentioning
confidence: 76%
“…The bands at 2923 and 1534 cm À1 attributed to O-H stretching of carboxylic acid and N À H bending of amide, respectively. The bands at 1221 and 1072 cm À1 corresponded to C À N and N-H stretching, respectively [18,19]. These results revealed that presented bacterial biomolecules in the CLS played an important role in the bioreduction of FTN.…”
Section: Characterizationmentioning
confidence: 76%
“…Hydrothermal processing is another approach due to its cost effectiveness and simplicity [102], nevertheless, green routes need to be developed to have a reliable supply in sufficient quantities without any harmful effects on the environment. TiO 2 -NPs are synthesized from plants [103], fungus [104], and piper betel leaf [105]. TiO 2 -NPs also exhibit antimicrobial activity by multiple mechanisms suggesting that the possibility of development of resistance by microbial cells against these nanoparticles is very low [10].…”
Section: Promising Biogenic Metallic Nanoparticles For Antibacterimentioning
confidence: 99%
“…In the past decade, there has been a marked increase in the field of synthesis of various nanoparticles such as metallic, metal oxide, nanocomposite, and decorated nanoparticles with controlled morphologies and remarkable features, making them an extensive area of research. e possibility of synthesizing NPs with controlled particle size, shape, and crystalline nature enables NPs to be used for various potential applications, such as degradation of organic pollutants in wastewater, biomedical, biosensor, catalyst for bacterial biotoxin elimination, and for the photoanode in dye-sensitized solar cells (DSSCs) [1][2][3]. Among the various adapted techniques for the synthesis of nanoparticles, biogenic synthesis of nanoparticles is an environmentally friendly protocol that involves the use of different parts and types of biogenic natural sources such as bacteria (intracellular and extracellular), fungi, yeast, virus, and different parts of green plants (flower, stem, root, leaf, and fruit) or the byproducts of their metabolism, which act as both reducing and stabilizing agents to prevent the overall growth of nanoparticles during their synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various adapted techniques for the synthesis of nanoparticles, biogenic synthesis of nanoparticles is an environmentally friendly protocol that involves the use of different parts and types of biogenic natural sources such as bacteria (intracellular and extracellular), fungi, yeast, virus, and different parts of green plants (flower, stem, root, leaf, and fruit) or the byproducts of their metabolism, which act as both reducing and stabilizing agents to prevent the overall growth of nanoparticles during their synthesis process. Moreover, metal oxide nanoparticles such as TiO 2 NPs obtained via this biogenic synthesis method, a greener approach synthesis method, are safe, nontoxic, ecofriendly, and achieved with minimum energy [2,3]. e natural environment suffers serious hazardous problems due to the release of different waste materials to the natural environment such as the accumulation of agricultural fruit and vegetable waste and industrial wastes (organic dyes, pesticides, inorganic contaminants and detergents) and due to the decomposition of toxic and poisonous gases and chemical species produced from chemical industries.…”
Section: Introductionmentioning
confidence: 99%